RESISTANCE OF ANOPHELES SACHAROVI FAVRE TO DDT - AV. Manouchehri; A.Zaini; E. Javadian; E. Saebi (Tehran University of Medical Sciences, 1973)
A.sacharovi, which is one of the main malaria vectors of the Palearchic region, is resistant to DDT in Greece (1949), Lebanon (1954), Turkey (1959), Syria and the U.S.S.R. (1972).The first record of A. sacharovi resistance to DDT in Iran was given in 1959 from the Kazeroon area, followed by Izeh (1969) and Meshkin-Shahr (1970).This study (1973) urgently advises speedy measures to eliminate the present foci of DDT -resistant A.sacharovi, to distinguish the checking of the susceptibility level of A. sacharovi in other areas of its distribution in Iran.